Proteomic analysis of plasma to identify novel biomarkers for intra-amniotic infection and/or inflammation in preterm premature rupture of membranes - Back, Ji Hyun; Kim, So Yeon; Gu, Man Bock; Kim, Hyeon Ji; Lee, Kyong-No; Lee, Ji Eun; Park, Kyo Hoon (Scientific reports, 2023)
To identify potential plasma biomarkers associated with microbial invasion of the amniotic cavity (MIAC) and/or intraamniotic inflammation (IAI) in women with preterm premature rupture of membranes (PPROM). This retrospective cohort study included 182 singleton pregnant women with PPROM (23–33 weeks) who underwent amniocentesis. Plasma samples; all subjects were chosen from these participants and were analyzed using label-free liquid chromatography-tandem mass spectrometry for proteome profiling using a nested case–control study design (cases with MIAC/IAI vs . non-MIAC/IAI controls [ n = 9 each]). Three identified target molecules for MIAC/IAI were further verified by ELISA in the study cohort ( n = 182). Shotgun proteomic analysis revealed 17 differentially expressed proteins ( P < 0.05) in the plasma of MIAC/IAI cases. In particular, the levels of FCGR3A and haptoglobin, but not LRP1, were found to be increased in the plasma of patients with MIAC, IAI, and both MIAC/IAI compared with those without these conditions. Moreover, these differences remained significant after adjusting for gestational age at sampling. The area under the curves of plasma FCGR3A and haptoglobin ranged within 0.59–0.65 with respect to each of the three outcome measures. Plasma FCGR3A and haptoglobin were identified as potential independent biomarkers for less-invasively detecting MIAC/IAI in women with PPROM.